Organization’s inadequate hiring Practices and employee performance in Puntland Region, Somalia (International Journal of Scientific Research and Management (IJSRM), 2025)
This study highlights the part that poor recruiting procedures have in organizational inefficiencies by examining the effects they have on worker performance in Puntland, Somalia. The study examines how ineffective hiring practices, such as a lack of job alignment and competency evaluation, compromise productivity, retention, and overall organizational performance by drawing on ideas such as Person-Job Fit and Human Capital. Data from 92 respondents in five varied firms using a correlational design and mixed-methods methodology highlight three major issues: gender inequality, talent mismatches, and hiring biases related to clan or familial ties. The results highlight the necessity of planned and open hiring practices to improve organizational results and worker quality. Suggestions are made to close these gaps and guarantee that job needs and staff competencies are in line.